(untitled) (Bangladesh Journal of Nuclear Medicine, 2018)
Superior mediastinal metastases are relatively uncommon findings in patients with well-differentiated thyroid cancer. We report a case of metastatic follicular variant of papillary thyroid cancer (FVPTC) in superior mediastinum which continued to produce thyroid hormone and was radioiodine avid without stimulation after thyroidectomy. A 62-year old woman presented for radio ablation therapy following thyroidectomy due to thyroid carcinoma. She underwent detailed examination including imaging and fine-needle aspiration cytology revealed a superior mediastinal mass of functioning metastasis from thyroid carcinoma. The post-therapeutic whole-body scan showed intense uptake of radioiodine (131I) in the metastatic lesion. A literature review reveals that FVPTC has a greater preponderance than papillary thyroid cancer (PTC) for distant metastases and that the majority of mediastinal metastases from either FVPTC or PTC are localized to the superior mediastinum. These lesions should be differentiated from the commonest mediastinal masses. They are very important to recognize as early recognition can lead to accurate and prompt diagnosis leading to timely treatment. The functioning metastases associated from differentiated thyroid cancer with euthyroidism or hyperthyroidism can be treated effectively with 131I without increasing TSH stimulation. Bangladesh J. Nuclear Med. 20(2): 143-150, July 2017